ChemInform Abstract: Assembly of Three Organic—Inorganic Hybrid Supramolecular Materials Based on Reduced Molybdenum(V) Phosphates. Issue 36 (9th September 2014) - Zhang, He; Yu, Kai; Lv, Jing‐Hua; Wang, Chun‐Mei; Wang, Chun‐Xiao; Zhou, Bai‐Bin
Abstract Three new supramolecular materials based on P4Mo6 polyoxoanions are hydrothermally prepared and their structures are determined by single crystal XRD.